ТЕОРЕТИЧЕСКИЕ ПОДХОДЫ К ИССЛЕДОВАНИЮ ВРЕМЕННОЙ КОМПЕТЕНТНОСТИ - Петрушка, А.Ю.; Смаглий, Т.И. (My University, 2019)
Аннотация Статья посвящена рассмотрению теоретических аспектов изучения временной компе- тентности. Авторами выявлены различные подходы к пониманию данного феномена, обоб- щены точки зрения ученых и уточнено его определение. Знание основных составляющих временной компетентности позволит в дальнейшем разработать психологические технологии ее формирования. Abstract The article is devoted to the consideration of the theoretical aspects of the study of temporal competence. The authors identified various approaches to understanding this phenomenon, summa- rized the points of view of scientists and clarified its definition. Knowledge of the main components of temporary competence will further develop the psychological technology of its formation.
Theoretical approaches to temporal competence research
Keywords: время; компетентность; временная компетентность; time; competence; time competence